Bridging Known and Unknown Unknowns: From Natural Products and Their Mimics to Unmet Needs in Neuroscience - Martin, Stephen F (Accounts of chemical research, 2022)
Scientific excursions into the unknown are often characterized by unanticipated twists and turns that may lead in directions that never could have been predicted. Decisions made during the course of these explorations determine what we discover. This Account chronicles one such journey that began with a challenge encountered during the synthesis of a natural product and then unfolded over more than 30 years to focus on unmet needs in neuroscience. Specifically, while developing a concise approach to tetrahydroalstonine, a heteroyohimboid alkaloid having α-adrenergic activity, we faced the predicament of assembling a key intermediate. Solving this problem resulted in the serendipitous discovery of the vinylogous Mannich reaction and a productive program wherein we used this powerful construction as a key step in the syntheses of numerous alkaloids. However, we also realized that lessons learned from the synthesis of tetrahydroalstonine could be generalized to invent a new strategy for preparing diverse collections of substituted nitrogen heterocycles that could be screened against biological targets. The approach featured the combination of several reactants in a multicomponent assembly process to give a functionalized intermediate that could be elaborated by various ring-forming reactions to give heterocyclic scaffolds that could be further diversified. Screening these compound sets against a broad range of biological targets revealed some intriguing hits, but none of them led to a productive collaboration in translational research. Notwithstanding this setback, we screened curated members of our collections against proteins in the central nervous system and discovered some substituted B-norbenzomorphans that were selective for the enigmatic sigma-2 receptor (σ R), an understudied protein that had been primarily associated with cancer. With scant knowledge of its role in neuroscience, we posited that small molecules that bind to σ R might be neuroprotective, thus launching a new venture. In parallel investigations we prepared analogues of the initial hits, explored their effects in animal models of neurodegenerative and neurological conditions, and identified σ R as transmembrane protein 97 (TMEM97). After first establishing the neuroprotective effects of several σ R/TMEM97 ligands in a transgenic model of neurodegeneration, we showed that one of these has procognitive effects and reduces levels of proinflammatory cytokines in a transgenic mouse model of Alzheimer's disease. We then identified a closely related σ R/TMEM97 ligand that mitigates hippocampal-dependent memory deficits, prevents axon degeneration, and protects neurons and oligodendrocytes after traumatic brain injury. In a recent study, this compound was shown to protect retinal ganglion cells from retinal ischemia/reperfusion injury. In other collaborative investigations, we have shown that related, but structurally distinct, σ R/TMEM97 ligands alleviate neuropathic pain, while a σ R/TMEM97 ligand representing yet another chemotype reduces impairments associated with alcohol withdrawal. More recently, we have shown that σ R/TMEM97 ligands enhance survival of cortical neurons in a neuronal model of Huntington's disease. Translational and mechanistic studies in these and other areas are in progress. Solving a problem we faced in natural product synthesis thus served as an unexpected gateway to discoveries that could lead to entirely new approaches to treat neurodegenerative and neurological conditions by targeting σ R/TMEM97, a protein that has never been associated with these afflictions.